Enhancing Caries Management with Silver Diamine Fluoride: A Comprehensive Review - Al Saffan, Abdulrahman Dahham (Asian Journal of Pharmaceutics (AJP), 2025)
Silver diamine fluoride (SDF) has emerged as an essential, non-invasive tool in modern dentistry, particularly for arresting caries and preventing further decay. Its effectiveness in pediatric, geriatric, and special needs populations has contributed to its growing acceptance in both clinical and public health settings. This narrative review focuses on the structure of SDF, its mechanism of action, clinical efficacy, safety, and its integration into dental practice. This review synthesizes recent research, offering significant insights into the potential application of SDF as a cornerstone of preventive dentistry and its impact on the advancement of caries management globally. Various electronic data bases such as PubMed, Scopus, Google scholar and Saudi digital library were utilized to search articles. A comprehensive search was conducted utilizing relevant keywords. The full-text articles discussing various aspects of SDF published in English language were reviewed for its composition, mechanism of action, clinical efficacy, safety profile, and future directions of SDF in dental care, highlighting its potential for addressing global oral health disparities. The review finding suggests that SDF represents a transformative advancement in contemporary dentistry, offering a cost-effective, non-invasive, and efficacious method for halting dental cavities. Its utilization in the management of caries among various demographics, including children, the elderly, and individuals with special needs, highlights its significance as a resource in clinical and community health frameworks